Study the velocity and pressure exerted in front of the filter surface in the kitchen hood system by using ANSYS - Asmuin, Norzelawati; Pairan, M. Rasidi; Mat Isa, Norasikin; Sies, Farid (2022)
Commercial kitchen hood ventilation system is a device used to capture and filtered the plumes from cooking activities in the kitchen area. Nowadays, it is very popular in the industrial sector such as restaurant and hotel to provide hygiene food. This study focused at the KSA filter part which installed in the kitchen hood system, the purpose of this study is to identify the critical region which indicated by observing the velocity and pressure of plumes exerted at of KSA filter. It is important to know the critical location of the KSA filter in order to install the nozzle which will helps increase the filtration effectiveness. The ANSYS 16.1 (FLUENT) software as a tool used to simulate the kitchen hood systems which consist of KSA filter. The commercial kitchen hood system model has a dimension 700 mm width, 1600 mm length and 555 mm height. The system has two inlets and one outlet. The velocity of the plumes is set to be 0.235m/s and the velocity of the inlet capture jet is set to be 1.078m/s. The KSA filter is placed 45 degree from the y axis. The result shows the plumes has more tendency flowing pass through at the bottom part of KSA filter.